The Role of the KPK TikTok Account in Building Anti-Corruption Awareness in South Kalimantan - Hayat, Muzahid Akbar; Khairunnisa, Devi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Corruption is a serious threat in Indonesia that hinders development and harms society, thus requiring various approaches for its mitigation, including through social media. The Corruption Eradication Commission (KPK) utilizes the TikTok platform to raise public awareness, especially in South Kalimantan, about the dangers of corruption and its prevention. This study aims to explore the role of the KPK's TikTok account in building anti-corruption awareness in the region and its impact on public perception. Using a literature review approach with a descriptive qualitative methodology, this research analyzes relevant sources, including journals, articles, and previous research reports. The findings show that TikTok has become an effective tool in spreading anti-corruption messages, particularly to the younger generation. The campaigns carried out by the KPK through TikTok provide education, promote transparency, and support public involvement in corruption prevention efforts. Additionally, public participation on social media, integrity-based training for civil servants, and anti-corruption education in schools further strengthen this campaign. However, its effectiveness can still be enhanced through collaboration with local communities and optimization of visual content. This study provides valuable insights into how social media, particularly TikTok, can be used to support transparency and drive sustainable anti-corruption efforts in South Kalimantan.